ALBANIA AND GREECE – POLITICAL AND DIPLOMATIC RELATIONS BETWEEN 1920-1930 - Komina, Bledar (European Scientific Journal, ESJ, 2014)
When we talk about political and diplomatic relations between Albania and Greece in the period 1920-1930, always we try to refer to state relations and political actors of both countries. For this period we can explain that the relations between the two countries have not been good, but are often characterized by tension, almost by the Greek state interference in the internal affairs of Albania. At the same time this troubled situation is characterized by tense political and diplomatic relations, further from the repressive policies pursued by Athens over Albanian Cham population, living in Northern Greece, otherwise called Northern Epirus. These relationships will draw the tense and characterizes politics and diplomacy of the two countries for almost two decades. Albania and Greece politicians and political leaders time after time tried to stabilize the situation. But Greece, which felt superior because of alliances that she had with the Great Powers, put conditions in order to stabilize the relations between two countries. While the Albanian state without any help from the Great Powers, try to protect his rights in relation to Greece, and in relation to the Greek minority living in Albania, providing them all possible rights stemming from the agreement that Albanian state had signed in 1921.